Twin Legacies: Victor and Vincent McKusick / Twin Studies: Twinning Rates I; Twinning Rates II; MZ Twin Discordance for Russell–Silver Syndrome; Twins' Language Skills / Headlines: Babies Born to Identical Twin Couples; Identity Exchange; Death of Princess Ashraf (Twin); Yahoo CEO Delivers Identical Twins. (3rd March 2016) - Segal, Nancy L.
Abstract : The lives of the illustrious monozygotic (MZ) twins, Victor A. and Vincent L. McKusick, are described. Victor earned the distinction as the 'Father of Medical Genetics', while Vincent was a legendary Chief Justice of the Maine Supreme Court. This dual biographical account is followed by two timely reports of twinning rates, a study of MZ twin discordance for Russell–Silver Syndrome (RSS) and a study of twins' language skills. Twin stories in the news include babies born to identical twin couples, a case of switched identity, the death of Princess Ashraf (Twin) and a new mother of twins who is also Yahoo's CEO.